Factors affecting in-vehicle exposure to traffic-related air pollutants: A review. (15th February 2023) - Campagnolo, Davide; Borghi, Francesca; Fanti, Giacomo; Keller, Marta; Rovelli, Sabrina; Spinazzè, Andrea; Cattaneo, Andrea; Cavallo, Domenico M.
Abstract: The aims of this review are: analyse the in-vehicle exposure determinants to traffic-related air pollutants (TRAPs); identify the lack of information in this field, providing suggestions for future surveys; discuss the applicability of innovative solutions for the reduction of in-vehicle exposure to TRAPs. Results: outlined that route, traffic and time-related variables are closely related to each other and mainly affect the in-cabin black carbon, carbon monoxide, particulate matter and ultrafine particles exposure levels. Self-pollution plays an important role in defining the in-vehicle exposure especially to volatile organic compounds. Ventilation settings resulted to be the main determinants of in-vehicle exposure to TRAPs. One of the gaps of knowledge identified concerns the impact of leading vehicles on in-cabin TRAPs concentrations. The study of in-cabin exposure determinant factors is useful to implement effective measures to mitigate high exposures inside vehicles: the most promising seems to be the development of responsive ventilation systems. Graphical abstract: Image 1 Highlights: Route, time and traffic characteristics are closely related to each other. Self-pollution plays a critical role in defining the in-cabin pollutants exposure. Ventilation settings is the main determinants of in-vehicle exposure to TRAPs. Gaps of knowledge: impact of leading vehicles on in-cabin TRAPs concentrations. Gaps of knowledge: factors associated to in-vehicle exposure to VOCs.